The Effects of Slope Height and Rain Intensity on the Stability and Cost of Retaining Walls: Pengaruh Ketinggian Lereng dan Intensitas Hujan Terhadap Stabilitas dan Biaya Dinding Penahan Tanah - Albab, Moch. Nurul Ulil; Mulyono, Bagyo; Apriyono, Arwan (Jurnal Rekayasa Sipil dan Lingkungan, 2025)
Slope failures frequently occur due to geomorphological, hydrological, and human activity factors. Retaining walls (DPT) can serve as a mitigation solution by resisting lateral soil pressure and preventing slope collapse. The critical factors influencing stability are slope height and rainfall intensity—increased height reduces stability, while rainfall weakens soil strength. Material selection is essential for optimizing both cost and performance. This study analyzes the influence of material type, slope height, and B/H ratio (0.3–0.7) on stability and cost using finite element and limit equilibrium methods. The retaining walls were constructed using two materials: stone masonry and reinforced concrete, with wall heights (H) ranging from 1.5 to 10 meters. The results indicate that every 0.5-meter increase in wall height reduces the safety factor (SF) by 5.61–6.53% for stone masonry and 5.47–6.08% for concrete. Stone masonry walls provide a higher SF, averaging 10.39% greater than reinforced concrete, with a more significant improvement in SF relative to the B/H ratio. Cost analysis reveals a linear relationship between SF and construction costs—higher safety factors require greater expenditures. Stone masonry retaining walls demonstrate higher stability and cost efficiency in achieving the minimum required SF compared to concrete walls. ABSTRAK Fenomena keruntuhan lereng yang sering terjadi akibat faktor geomorfologi, hidrologi, dan aktivitas manusia. Dinding Penahan Tanah (DPT) dapat menjadi solusi sebagai langkah mitigasi. DPT berfungsi menahan tekanan lateral tanah dan mencegah keruntuhan lereng, dengan ketinggian lereng dan intensitas hujan sebagai faktor kritis. Peningkatan ketinggian menurunkan stabilitas, sementara hujan mengurangi kekuatan tanah. Pemilihan material penting untuk optimasi biaya dan kinerja. Penelitian ini bertujuan menganalisis pengaruh material, ketinggian lereng, dan rasio B/H (0,3–0,7) terhadap stabilitas dan biaya menggunakan metode elemen hingga dan kesetimbangan batas. Material DPT yang digunakan adalah pasangan batu kali dan beton bertulang, dengan tinggi lereng DPT (H) 1,5-10 m. Hasil menunjukkan bahwa setiap penambahan ketinggian DPT 0,5 m mengakibatkan penurunan faktor keamanan (SF) sebesar 5,61–6,53% (pasangan batu kali) dan 5,47–6,08% (beton). DPT pasangan batu kali memberikan SF lebih tinggi rata-rata 10,39% dibanding beton, dengan peningkatan SF lebih signifikan terhadap rasio B/H. Analisis biaya menunjukkan bahwa terdapat hubungan linier antara SF dan biaya konstruksi, semakin tinggi SF maka biaya yang dibutuhkan semakin tinggi. DPT pasangan batu kali memberikan stabilitas yang lebih tinggi dan efisien untuk SF minimum.